Spatially Bandgap-Graded MoS2(1−x)Se2x Homojunctions for Self-Powered Visible–Near-Infrared Phototransistors - Xu, Hao; Zhu, Juntong; Zou, Guifu; Liu, Wei; Li, Xiao; Li, Caihong; Ryu, Gyeong Hee; Xu, Wenshuo; Han, Xiaoyu; Guo, Zhengxiao; Warner, Jamie H.; Wu, Jiang; et al. (Nano-Micro Letters, 2020)
Ternary transition metal dichalcogenide alloys with spatially graded bandgaps are an emerging class of two-dimensional materials with unique features, which opens up new potential for device applications. Here, visible–near-infrared and self-powered phototransistors based on spatially bandgap-graded MoS2(1−x)Se2x alloys, synthesized by a simple and controllable chemical solution deposition method, are reported. The graded bandgaps, arising from the spatial grading of Se composition and thickness within a single domain, are tuned from 1.83 to 1.73 eV, leading to the formation of a homojunction with a built-in electric field. Consequently, a strong and sensitive gate-modulated photovoltaic effect is demonstrated, enabling the homojunction phototransistors at zero bias to deliver a photoresponsivity of 311 mA W−1, a specific detectivity up to ~ 1011 Jones, and an on/off ratio up to ~ 104. Remarkably, when illuminated by the lights ranging from 405 to 808 nm, the biased devices yield a champion photoresponsivity of 191.5 A W−1, a specific detectivity up to ~ 1012 Jones, a photoconductive gain of 106–107, and a photoresponsive time in the order of ~ 50 ms. These results provide a simple and competitive solution to the bandgap engineering of two-dimensional materials for device applications without the need for p–n junctions. Highlights: 1 Due to the Se composition and thickness gradient within single MoS2(1−x)Se2x domains, the bandgap of MoS2(1−x)Se2x is gradually tuned from 1.83 to 1.73 eV. 2 The homojunction phototransistors at zero bias deliver a photoresponsivity of 311 mA W−1, a specific detectivity up to ~ 1011 Jones, and an on/off ratio up to ~ 104. 3 The biased devices yield a champion photoresponsivity of 191.5 A W−1, a specific detectivity up to ~ 1012 Jones, and a photoconductive gain of 106–107.